ANALISIS ANGGARAN PARSIAL PENGGUNAAN PUPUK BOKASI DAN SUPER ACI PADA TANAMAN CABAI - Krisna Setiawan; Ferdy A. I. Fallo (Partner, 2008)
Parsial Budget Analysis applies fertilizer Bokasi and Super ACI to Chilli Crop. This research aim to feasibility analysis be financial to influence applies fertilizer Bokasi and Super ACI to chilli crop. This research executed in Screen House property of Politeknik Pertanian Negeri Kupang. Variable observed covers amount and the price of input applied, number of from fresh chillies yielded, the price of result of produce of chilli, advantage of dirty per check and net profit per check and rate of return marjinal per check. Data obtained will be analysed by using parsial budget analytical method. Result of research indicates that applies fertilizer Bokasi and Super ACI in chilli farming told to be competent financially. This thing shown by added value 1,27 for treatment of Super ACI and added value 1,15 for treatment Bokasi. The condition indicates that acceptance of bigger marjinal cleanness than costs changes marjinal as result of treatment of Bokasi and Super ACIKey words: persial budget, fertilizer, chilli